(untitled) (KYAMC Journal, 2019)
Background: The outcome of the radiotherapy is highly dependent on how precisely dose is delivered to the tumor and should not exceed±5% of the prescribed dose including all types of uncertainties involved in the treatment procedure. Objectives: This manuscript describes the comprehensive Quality Assurance (QA) program for two linear accelerators by ensuring Percentage Depth Dose (PDD), Quality Index (QI), Beam Flatness and Symmetry, and beam output consistency at Khwaja Yunus Ali Medical College and Hospital, Sirajganj, Bangladesh. The program is designed according to the policy of the center and by the guidelines of Bangladesh Atomic Energy Regulatory Authority. Materials and Methods: The adopted QA procedure at our center included daily, weekly, monthly, and yearly checks, as well as individual treatment verifications and participation in IAEA/WHO TLD inter-comparison Program. Results: The results of the study showed reproducibility in all QA procedures with an average photon for monthly beam output 0.988±0.011, 0.989±0.010 and 1.005±0.006 for 4 MV, 6 MV and 15 MV respectively. The maximum variation of calibration factors of the chambers for last five years between the manufacturer values and the average calibration coefficient lies within -0.298 to 0.47% with an uncertainty of ±1.8% (k=1). The results of IAEA/WHO TLD inter-comparison program of dose measurement shows the ratio of IAEA to KYAMCH values was 1.009±0.018. Conclusion: The above result shows an excellent agreement of calibration coefficient of ionization chambers and dosimetry with the international standard system KYAMC Journal Vol. 10, No.-3, October 2019, Page 147-151